Introduction to the Special Issue on Archiving Sociolinguistic Data. Issue 11 (November 2014) - Yaeger‐Dror, Malcah; Cieri, Christopher
Abstract Advances in online networking have permitted an increasing interest in big data by the community of linguists. This special issue will address the needs of researchers hoping to take advantage of this expansion of our horizons, both by adapting their research design to permit their own corpus to conform to the expanded need for accurate metadata and to permit them to take full advantage of their own corpora that researcher can collect and analyze directly. In linguistics, this naturally leads to increased emphasis on data sharing, which is one way to amass data of sufficient size and variety to permit new kinds of insight. At the same time, there is a growing consensus among sociolinguists that researchers must refine their views on demographic, situational, and attitudinal factors that correlate with linguistic differences in order to permit not only more effective data sharing and comparison but also more accurate conclusions.